TUJUAN, PROSEDUR, DAN MODEL EVALUASI KURIKULUM: PERSPEKTIF KAJIAN SISTEMATIS - Ananda, Reza; Yusadi, Ardini; Zein, Wahyuli Lius (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2024)
Curriculum evaluation is a strategic process to assess the effectiveness, efficiency, relevance, and feasibility of an educational program. This study aims to provide a systematic overview of the objectives, procedures, and models of curriculum evaluation based on a literature review. The objectives of evaluation include program improvement, accountability to stakeholders, and determining follow-up actions for curriculum development outcomes. Evaluation procedures consist of methodological steps, both quantitative and qualitative, encompassing problem identification, data collection, result analysis, and recommendation formulation. Relevant curriculum evaluation models include Measurement, Congruence, Illumination, Educational System Evaluation, the CIPP model (Context, Input, Process, Product), and the Microeconomic model. Each model offers a different approach, ranging from cognitive measurement to holistic evaluations based on context, processes, and outcomes. This study reveals that the selection of an evaluation model should align with specific objectives, program needs, and the conditions of curriculum implementation. The findings of this study provide a systematic guide for improving the design and implementation of curriculum evaluation across educational units. Thus, this research is expected to support continuous efforts to enhance the quality of education.